(untitled) (LEGAL DIALOGICA, 2025)
This study examines the Criminal Liability of Corporations for Aviation Negligence Resulting in Death. This study uses a normative research method, research conducted with an approach to legal norms or substances, legal principles, legal theory, legal arguments and comparative law. The results of the study indicate that the criminal liability of corporations for negligence resulting in loss of life is that the corporation is responsible in other words that criminal acts in the field of aviation are considered to be committed by the corporation if the crime is committed by a person acting for and/or on behalf of the corporation or for the benefit of the corporation, corporate liability is imprisonment and fines for its managers based on Article 441 of Law No. 1 of 2009 and the Board of Directors of civil airline companies can be criminally liable in the event of a plane crash that results in fatalities because the board of directors is an important organ in the company, in accordance with Article 1 number 5 of the PT Law which states that the board of directors as a company organ has the authority and full responsibility for managing the company for the benefit of the company. Any director who is proven to have neglected to carry out their duties or intentionally committed an aviation crime should be punished. Writing recommendations: (1) For the government, Law Number 1 of 2009 concerning Aviation, as a legal umbrella in the aviation sector, must be implemented in its entirety as it should be. Therefore, aviation crimes must be resolved according to criminal law; (2) In order for criminal penalties to be on target, it is necessary to update the aviation law by clearly stating which directors must be punished and what actions are prohibited in detail to clarify the limits of criminal liability of directors and other managers. Abstrak: Penelitian ini mengkaji tentang Pertanggung Jawaban Pidana Korporasi Terhadap Kelalaian Penerbangan Yang Mengakibatkan Kematian. Penelitian ini menggunakan metode penelitian penelitian normatif, penelitian yang dilakukan dengan pendekatan pada norma atau substansi hukum, asas hukum, teori hukum, dalil-dalil hukum dan perbandingan hukum. Hasil penelitian menunjukkan bahwa Pertanggungjawaban pidana korporasi terhadap kelalaian yang mengakibatkan hilangnya nyawa yaitu bahwa korporasi bertanggung jawab dengan kata lain bahwa tindak pidana di bidang penerbangan dianggap dilakukan oleh korporasi apabila tindak pidana tersebut dilakukan oleh orang yang bertindak untuk dan/atau atas nama korporasi atau untuk kepentingan korporasi, pertanggungjawaban korporasi yaitu pidana penjara dan denda terhadap pengurusnya berdasarkan Pasal 441 UU No. 1 Tahun 2009 dan Direksi perusahaan maskapai penerbangan sipil dapat bertanggungjawab secara pidana apabila terjadi kecelakaan pesawat yang menimbulkan korban jiwa karena direksi merupakan organ penting dalam perusahaan, sesuai dengan Pasal 1 angka 5 UU PT yang menegaskan, direksi sebagai organ perseroan berwenang dan bertanggung jawab penuh atas pengurusan perseroan untuk kepentingan perseroan. Setiap direksi yang terbukti lalai menjalankan tugasnya atau sengaja dalam melakukan tindak pidana penerbangan seharusnya dipidana. Rekomendasi penulisan : (1) Bagi pemerintah bahwa Undang-Undang Nomor 1 Tahun 2009 tentang Penerbangan, sebagai payung hukum di bidang penerbangan harus diterapkan secara keseluruhan sebagai mana semestinya. Sehingga, tindak pidana penerbangan harus diselesaikan sesuai jalur hukum pidana; (2) BAgar pemidanaan tepat sasaran, perlu kiranya dilakukan pembaharuan undang-undang penerbangan dengan menyatakan jelas pengurus yang mana yang harus dipidana serta perbuatan apa saja yang dilarang secara rinci supaya jelas mengenai batas pertanggungjawaban pidana direksi dan pengurus lainnya.